2016
DOI: 10.1158/2159-8290.cd-15-1183
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell–Driven Extracellular Matrix Remodeling Drives Haptotaxis during Metastatic Progression

Abstract: Fibronectin (FN) is a major component of the tumor microenvironment, but its role in promoting metastasis is incompletely understood. Here we show that FN gradients elicit directional movement of breast cancer cells, in vitro and in vivo. Haptotaxis on FN gradients requires direct interaction between α5β1 integrin and Mena, an actin regulator, and involves increases in focal complex signaling and tumor-cell-mediated extracellular matrix (ECM) remodeling. Compared to Mena, higher levels of the pro-metastatic Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
187
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(194 citation statements)
references
References 48 publications
3
187
0
Order By: Relevance
“…Some of the newer generation microfluidic devices incorporate pumps that provide a continuous flow of the soluble gradient and permit intermittent fluid analysis (Wu et al 2012), whereas others generate long-term stable gradients and have revealed that subtle differences in gradients can exert significant biological effects (Suraneni et al 2012). Stable ECM haptotactic gradients have also been developed using microfluidics and used to study 2D and 3D responses to multiple ECM cues such as FN, laminin, and vitronectin (Chan et al 2014;Oudin et al 2016a). Microfluidic channel width can also be used to directly modulate collagen alignment.…”
Section: New Advances In Microfluidicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the newer generation microfluidic devices incorporate pumps that provide a continuous flow of the soluble gradient and permit intermittent fluid analysis (Wu et al 2012), whereas others generate long-term stable gradients and have revealed that subtle differences in gradients can exert significant biological effects (Suraneni et al 2012). Stable ECM haptotactic gradients have also been developed using microfluidics and used to study 2D and 3D responses to multiple ECM cues such as FN, laminin, and vitronectin (Chan et al 2014;Oudin et al 2016a). Microfluidic channel width can also be used to directly modulate collagen alignment.…”
Section: New Advances In Microfluidicsmentioning
confidence: 99%
“…Intravital imaging studies in mice containing needles with EGF have shown that cells enter the needle by active migration only ). Since its inception this assay has been used to study both chemotactic and haptotactic responses (Oudin et al 2016a). More recently, a new microscale device was developed which incorporates multiple reservoirs in the delivery system to permit the time-resolved delivery of several compounds.…”
Section: Visualizing and Measuring Directional Migration In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…During the remodeling process, a tugging force is generated on the surrounding collagen fibers as they are bundled and arranged (Castella et al, 2010;Goffin et al, 2006;Murrell et al, 2015;Oudin et al, 2016). The presence of the myofibroblasts and the forces they generate have been linked to increased cancer cell invasion and motility (De Wever et al, 2008;Elkabets et al, 2011;Fuyuhiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After perforating the basement membrane, the escaped cancer cells then must invade the ECM and travel through a meshwork of randomly oriented collagen fibers prior to intravasation into a blood vessel [8]. While maneuvering through the ECM, the direction and behavior of the migrating cells are greatly influenced by the physical and biomechanical properties of the ECM [9][10][11].…”
Section: Introductionmentioning
confidence: 99%